1980
DOI: 10.1111/j.2044-8341.1980.tb01432.x
|View full text |Cite
|
Sign up to set email alerts
|

A predictive study of post‐partum depression: Some predisposing characteristics

Abstract: Postnatal depression was investigated by the antenatal screening of a sample of women for factors that might be predictive of later disturbance. The women were assessed when they were 36 weeks pregnant on anxiety, hostility, and locus of control. Predictions were tested by assessing depression 6 weeks after birth. Both high anxiety and high hostility were positively associated with postnatal depression. Intropunitiveness was not significantly related to subsequent depression. The most depressed women were thos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
33
1
2

Year Published

1982
1982
2007
2007

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(38 citation statements)
references
References 7 publications
2
33
1
2
Order By: Relevance
“…This lends some limited support to the premise of a link between externality and dysphoric response to the stress of a presumably positive critical event, with the association more clearly emerging during the period of actual coping than during the period of anticipation. This finding is in line with the results of those studies of another positive critical life event, the transition to motherhood, which point to a significant tie between postpartum depression and prepartum attributional style (O'Hara, Rehm, & Campbell, 1982) or locus of control (Hayworth et al, 1980).…”
Section: Discussionsupporting
confidence: 82%
“…This lends some limited support to the premise of a link between externality and dysphoric response to the stress of a presumably positive critical event, with the association more clearly emerging during the period of actual coping than during the period of anticipation. This finding is in line with the results of those studies of another positive critical life event, the transition to motherhood, which point to a significant tie between postpartum depression and prepartum attributional style (O'Hara, Rehm, & Campbell, 1982) or locus of control (Hayworth et al, 1980).…”
Section: Discussionsupporting
confidence: 82%
“…Post-partum mood has also been related to variables such as anxiety during pregnancy (Dennerstein et al, 1989;Elliot et al, 1984;Hayworth et al, 1980), breastfeeding (Alder and Cox, 1983;Dennerstein et al, 1989), past history of psychiatric disorders (Ballinger, 1982;Paykel et al, 1980), premenstrual mood changes (Dennerstein et al, 1989), depression during pregnancy (Buesching et al, 1986;Dennerstein et al, 1989), housing problems (Oakley, 1980;Paykel 1980). Major factors in post-partum depressive complaints or unhappiness after childbirth seem to be a lack of support, especially by the partner, or marital problems (Dennerstein et al, 1989;O'Hara, 1987;Romito, 1989).…”
Section: Post-partum Well-beingmentioning
confidence: 97%
“…The authors concluded that the incidence of 'neurotic' depression increased in early pregnancy and in the first three months postpartum; additionally, they noted that subjects usually suffered from either antenatal or postnatal depression, not both. In an investigation of the predictors of postpartum depression, Hayworth and others noted that women experiencing depression at 6 weeks postpartum (measured with a self-rating depression scale) tended also to have experienced depression at 36 weeks of pregnancy (Hayworth et al, 1980). Using the Beck Depression Inventory (BDI - Beck et al, 1961), recent reports documented no significant change in the level of depression between prepartum and postpartum measurements (Atkinson and Rickel, 1984;Manly et a1.,1982;O'Hara et a1.,1982).…”
mentioning
confidence: 97%